An ore blending structure and smelting method of a full-process vanadium-titanium sintered ore
Patent Information
- Application Number
- CN202411010063.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-07-26
AI Technical Summary
[0004]针对现有技术中烧结矿的配矿方法存在的成本高,以及为了降低成本会降低烧结矿质量,给高炉冶炼带来困难等问题,本发明提供一种全流程钒钛烧结矿的配矿结构及冶炼方法
[0053]This invention comprehensively considers the quality of sintered ore, the smooth operation of blast furnace smelting, and the improvement of efficiency and quality in the entire process of iron smelting and steelmaking. It provides a novel vanadium-titanium sinter blending structure. By adjusting the blending structure and proportions, and using multiple raw materials mixed in specific amounts, it not only ensures the grade of sintered ore and the smooth operation of blast furnace smelting, but also makes full use of inexpensive low-quality iron ore resources and steel slag waste, thereby effectively reducing smelting costs. Simultaneously, the blending structure provided by this invention can effectively increase the vanadium content in the molten iron, reducing the amount of ferrovanadium alloy used. Furthermore, the steel slag obtained from smelting can be recycled as a raw material for the blending structure, reducing blending costs and waste generation. By adopting the unique blending structure, blast furnace charging, and smelting process provided by this invention, a comprehensive reduction in the cost of sintered ore raw materials, iron smelting, and steelmaking alloys is achieved. The cost of molten iron is reduced by 11 yuan/ton, and the cost of steelmaking is reduced by 0.68 yuan/ton. This improvement in quality while reducing overall process costs demonstrates high economic and environmental benefits and has significant potential for widespread application.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of smelting technology, and in particular to a ore blending structure and smelting method for vanadium-titanium sinter throughout the entire process. Background Technology
[0002] In the iron and steel metallurgy industry, iron ore powder, coke, flux, and other materials are mixed with water and then granulated using a cylindrical mixer to obtain small pellets with a specific particle size distribution. These pellets are then sintered on a blast furnace using suction sintering to ultimately obtain the sinter required for blast furnace ironmaking. As a crucial component of blast furnace feed, the quality of sinter directly affects the blast furnace's production efficiency and cost. Sinter typically accounts for over 80% of the feed; therefore, its quality plays a decisive role in the production and smooth operation of the blast furnace.
[0003] Most enterprises reduce iron ore costs at the sintering stage by transitioning from high-quality to cost-effective materials. However, using cost-effective materials inevitably leads to an increase in harmful elements (such as titanium, potassium, sodium, and zinc) in the iron ore, reducing the quality of the sinter and creating difficulties for blast furnace smelting. Therefore, providing a sinter blending method that ensures stable sinter quality and reduces production costs is of great significance for guiding cost reduction and efficiency improvement in sintering production. Summary of the Invention
[0004] To address the problems of high cost and reduced sinter quality in existing sinter blending methods, which pose challenges to blast furnace smelting, this invention provides a complete vanadium-titanium sinter blending structure and smelting method. The blending structure provided by this invention results in sinter of stable quality. This furnace charge structure enables long-term stable operation of the blast furnace, reduces ironmaking costs, and offers significant economic benefits, demonstrating high practical value.
[0005] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: In a first aspect, the present invention provides a complete vanadium-titanium sintering ore blending structure, wherein the raw materials for the vanadium-titanium sintering ore include sintered iron charge, flux, and fuel. Based on 100% of the vanadium-titanium sintered ore, the sintered iron material comprises the following raw material components by mass percentage: 4%~7% iron concentrate, 7%~11% high vanadium-titanium iron powder, 29%~40% external ore powder, 1%~2.5% steel slag, 0%~2% iron scale, 2%~3% aluminum powder, 1%~3% boron-magnesium iron powder, and 0%~2% pyrite powder; The iron concentrate includes ordinary iron powder and 69 iron powder; the high vanadium titanium iron powder has the following mass percentage composition: TFe 65%~67%, SiO2 2.6%~3.6%, CaO 0.9%~1.9%, MnO 0.08%~0.12%, MgO 0.2%~0.5%, Al2O3 0.8%~1.1%, TiO2 0.8%~2.2%, V 0.19%~0.24%, with the balance being unavoidable impurities; The mass percentage of the external mineral powder components is as follows: TFe 55%~65%, SiO2 3.6%~6.6%, CaO 0.01%~0.21%, MnO 0.08%~0.8%, MgO 0.1%~0.17%, Al2O3 0.6%~5.9%, TiO2 0.02%~0.23%, V 0.001%~0.012%, with the balance being unavoidable impurities.
[0006] Compared to existing technologies, the ore blending structure of the vanadium-titanium sinter provided by this invention, through adjusting the blending structure and ratio, uses high-content external ore powder and a small amount of iron concentrate, high-vanadium-titanium iron-vanadium, and boron-magnesium iron powder as the main raw materials, and adds a certain amount of steel slag and aluminum powder. Under the premise of ensuring the quality of sinter and the smooth operation of blast furnace smelting, the amount of low-grade ore powder added is increased, realizing the resource utilization of steel slag and effectively reducing the blending cost of sinter. In addition, the above-mentioned ore blending structure can effectively increase the vanadium content in molten iron, which can reach more than 0.14%, thereby reducing the amount of vanadium-titanium alloy used. The cost of molten iron can be reduced by 11 yuan / ton, and the cost of steelmaking can be reduced by 0.68 yuan / ton, thereby effectively improving the market competitiveness of enterprises and having high practical value.
[0007] Furthermore, taking the vanadium-titanium sintered ore as 100% as raw material, the content of ordinary iron powder is 3%~5%, and the content of 69 iron powder is 1%~2%; wherein, the mass percentage of the ordinary iron powder is: TFe 65%~67%, SiO2 4%~4.5%, CaO 1.3%~1.5%, MnO 0.08%~0.12%, MgO 0.3%~0.5%, Al2O3 0.7%~0.9%, TiO2 0.8%~1.0%, V 0.13%~0.14%, with the balance being unavoidable impurities.
[0008] Furthermore, the mass percentage of the 69 iron powder is as follows: TFe 68%~70%, SiO2 1.9%~2%, CaO 0.3%~0.5%, MnO 0.08%~0.12%, MgO 0.1%~0.3%, Al2O3 0.6%~0.7%, TiO2 0.6%~0.7%, V 0.08%~0.09%, with the balance being unavoidable impurities.
[0009] Furthermore, based on 100% of the raw material of the vanadium-titanium sinter, the high-vanadium-titanium iron powder includes 2%~3% of the first iron powder, 3%~4% of the second iron powder, 1%~2% of the third iron powder, and 1%~2% of the fourth iron powder; The first iron powder component has the following mass percentages: TFe 65%~66%, SiO2 3.5%~3.6%, CaO 1.7%~1.9%, MnO 0.08%~0.12%, MgO 0.3%~0.5%, Al2O3 0.9%~1.1%, TiO2 0.9%~1.1%, V 0.23%~0.24%, with the balance being unavoidable impurities.
[0010] In one specific embodiment of the present invention, the first iron powder may be Baotong high vanadium iron powder from Beijing Huaxia Jianlong Mining Technology Co., Ltd.
[0011] Furthermore, the mass percentage of the second iron powder component is as follows: TFe 66%~67%, SiO2 2.6%~2.8%, CaO 0.9%~1.1%, MnO 0.08%~0.12%, MgO 0.2%~0.4%, Al2O3 0.8%~0.9%, TiO2 2%~2.2%, V 0.19%~0.2%, with the balance being unavoidable impurities.
[0012] In one specific embodiment of the present invention, the second iron powder may be Yuantong Jianlong high vanadium iron powder from Beijing Huaxia Jianlong Mining Technology Co., Ltd.
[0013] Furthermore, the mass percentage of the third iron powder component is as follows: TFe 65%~67%, SiO2 3%~3.5%, CaO 1.6%~1.8%, MnO 0.08%~0.12%, MgO 0.2%~0.4%, Al2O3 0.9%~1.1%, TiO2 0.8%~0.9%, V 0.23%~0.24%, with the balance being unavoidable impurities.
[0014] In one specific embodiment of the present invention, the third iron powder may be Baitong Jianlong high vanadium iron powder from Beijing Huaxia Jianlong Mining Technology Co., Ltd.
[0015] Furthermore, the mass percentage of the third iron powder component is as follows: TFe 65%~66%, SiO2 3%~3.5%, CaO 1.4%~1.5%, MnO 0.08%~0.12%, MgO 0.3%~0.5%, Al2O3 0.9%~1.1%, TiO2 1.6%~1.7%, V 0.23%~0.24%, with the balance being unavoidable impurities.
[0016] In one specific embodiment of the present invention, the third iron powder may be Luanping Jianlong high vanadium iron powder from Beijing Huaxia Jianlong Mining Technology Co., Ltd.
[0017] Furthermore, based on 100% of the raw material of the vanadium-titanium sinter, the high vanadium-titanium iron powder comprises 2%~4% of the first ore powder, 5%~7% of the second ore powder, 5%~6% of the third ore powder, 10%~12% of the fourth iron powder, 5%~7% of the fifth ore powder, and 2%~4% of the sixth ore powder; The first mineral powder component has the following mass percentages: TFe 62%~64%, SiO2 3.6%~3.8%, CaO 0.19%~0.21%, MnO 0.08%~0.12%, MgO 0.12%~0.14%, Al2O3 2.1%~2.3%, TiO2 0.04%~0.06%, V 0.001%~0.003%, with the balance being unavoidable impurities.
[0018] In one specific embodiment of the present invention, the first mineral powder is non-standard carbide powder from Hebei Jinxi International Trade Co., Ltd.
[0019] The second mineral powder component has the following mass percentages: TFe 60%~62%, SiO2 3.8%~4%, CaO 0.08%~0.1%, MnO 0.2%~0.4%, MgO 0.14%~0.16%, Al2O3 2.2%~2.4%, TiO2 0.04%~0.06%, V 0.002%~0.004%, with the balance being unavoidable impurities.
[0020] In one specific embodiment of the present invention, the second mineral powder is Rio Tinto's PB powder.
[0021] The mass percentage of the third mineral powder component is as follows: TFe 57%~59%, SiO2 5.7%~5.9%, CaO 0.01%~0.02%, MnO 0.2%~0.4%, MgO 0.14%~0.16%, Al2O3 2.7%~2.8%, TiO2 0.04%~0.06%, V 0.008%~0.012%, with the balance being unavoidable impurities.
[0022] In one specific embodiment of the present invention, the third mineral powder is a mixed powder from Hebei Jinxi International Trade Co., Ltd.
[0023] The mass percentage of the fourth mineral powder component is as follows: TFe 55%~57%, SiO2 6.1%~6.3%, CaO 0.07%~0.09%, MnO 0.2%~0.4%, MgO 0.12%~0.14%, Al2O3 5.7%~5.9%, TiO2 0.21%~0.23%, V 0.005%~0.007%, with the balance being unavoidable impurities.
[0024] In one specific embodiment of the present invention, the fourth mineral powder is 56 Indian powder from Hebei Jinxi International Trade Co., Ltd.
[0025] The mass percentage of the fifth mineral powder component is as follows: TFe 55%~56%, SiO2 6.1%~6.3%, CaO 0.08%~0.1%, MnO 0.6%~0.8%, MgO 0.15%~0.17%, Al2O3 2.8%~3%, TiO2 0.08%~0.12%, V 0.003%~0.005%, with the balance being unavoidable impurities.
[0026] In one specific embodiment of the present invention, the fifth mineral powder is a super-fine powder from Hebei Jinxi International Trade Co., Ltd.
[0027] The sixth mineral powder component has the following mass percentages: TFe 63%~65%, SiO2 6.5%~6.6%, CaO 0.07%~0.09%, MnO 0.08%~0.12%, MgO 0.1%~0.12%, Al2O3 0.6%~0.7%, TiO2 0.02%~0.04%, V 0.003%~0.005%, with the balance being unavoidable impurities.
[0028] In one specific embodiment of the present invention, the sixth mineral powder is Australian mineral powder from Hebei Jinxi International Trade Co., Ltd.
[0029] Furthermore, the mass percentage of the steel slag components is as follows: TFe 21%~23%, SiO2 11%~13%, CaO 23%~25%, MnO 1%~3%, MgO 4%~6%, Al2O3 3%~5%, TiO2 2.5%~2.7%, V 0.84%~0.86%, with the balance being unavoidable impurities.
[0030] Furthermore, the mass percentage of the iron sheet components is as follows: TFe 72%~73%, SiO2 1.4%~1.6%, CaO 0.01%~0.02%, MnO 0.2%~0.4%, MgO 0.1%~0.2%, Al2O3 0.9%~1.1%, TiO2 0.05%~0.07%, V 0.01%~0.03%, with the balance being unavoidable impurities.
[0031] Furthermore, the mass percentage of the aluminum powder composition is as follows: TFe 47%~48%, SiO2 3.1%~3.2%, CaO 0.5%~0.7%, MnO 0.08%~0.12%, MgO 0.18%~0.2%, Al2O3 10%~12%, TiO2 4.1%~4.3%, V 0.11%~0.13%, with the balance being unavoidable impurities.
[0032] Furthermore, the mass percentage content of the powder components is as follows: TFe 60%~61%, SiO2 3%~5%, CaO 0.1%~0.3%, MnO 0.1%~0.3%, MgO 0.1%~0.13%, Al2O3 2.1%~2.3%, TiO2 0.05%~0.07%, V 0.001%~0.003%, with the balance being unavoidable impurities.
[0033] Furthermore, the mass percentage of the boron-magnesium-iron powder is as follows: TFe 54%~55%, SiO2 4%~6%, CaO 0.2%~0.4%, MnO 0.08%~0.12%, MgO 10%~11%, Al2O3 0.2%~0.3%, TiO2 0.08%~0.1%, V 0.004%~0.006%, with the balance being unavoidable impurities.
[0034] Furthermore, the vanadium-titanium sinter content in the blast furnace charge is 70%~75% by mass, the pellet content is 15%~20% by mass, and the lump ore content is 5%~15% by mass.
[0035] Furthermore, the vanadium-titanium sinter has a particle size of 18-22 mm, the pellets have a particle size of 8-12 mm, and the lump ore has a particle size of 14-18 mm.
[0036] Furthermore, based on 100% of the raw material of the vanadium-titanium sinter, the flux includes 1% to 1.5% limestone, 4% to 4.5% quicklime, and 5% to 5.5% dolomite powder; the fuel content is 3.5% to 4%.
[0037] Specifically, the main components of the dolomite powder are: SiO2 2%, CaO 30%, MgO 20.8%, and Al2O3 0.33%.
[0038] Specifically, the fuel is coke powder.
[0039] In this invention, a certain amount of aluminum powder is added to reduce costs. However, a high aluminum content in blast furnace slag will result in high slag viscosity, affecting the smooth operation of blast furnace smelting. To increase the permeability of the blast furnace softening zone and the blast furnace slag discharge capacity, the content of dolomite powder is increased, thereby improving the smooth operation of blast furnace smelting under the ore blending structure of this invention.
[0040] Secondly, the present invention also provides a blast furnace smelting method for vanadium-titanium magnetite, the method comprising blast furnace smelting of blast furnace charge, wherein the blast furnace charge comprises the ore blending structure of the full-process vanadium-titanium sinter as described in any of the above-mentioned embodiments.
[0041] Furthermore, during the sintering process of the blast furnace charge, the material layer height is controlled at 790mm~810mm, the moisture content of the mixture is controlled at 7.1%~7.3%, the sintering machine speed is 2.1m / min~2.3m / min, the sintering speed is 19mm / min~20mm / min, the sintering temperature is 1250℃~1280℃, and the holding time is 120s~180s.
[0042] Furthermore, the sintering process pressure is -14kPa to -15kPa, the sintering endpoint temperature is 410℃ to 430℃, and the drum occupancy rate is 77% to 78%.
[0043] Optimal control of the blast furnace sintering process can improve the quality of sinter and ensure its strength.
[0044] Furthermore, the blast furnace charge distribution angles are as follows: the ore platform angle is 5°~9.5°, and the coke platform angle is 8°~11°; the maximum coke distribution angle is greater than the maximum ore distribution angle, and the minimum coke distribution angle is less than the minimum ore distribution angle; the ore and coke levels include 5~6 levels, and as the level increases, the coke and ore distribution angles decrease sequentially, with the ore distribution angles of adjacent levels differing by 1°~3°, and the coke distribution angles of adjacent levels differing by 1°~3° except for the central coke; the central coke angle is 10°~15°, and the proportion of central coke in the total coke is 24%~26%.
[0045] Furthermore, the minimum coke feeding angle is 1° smaller than the minimum ore feeding angle, and the maximum coke feeding angle is 0.5°~1° larger than the maximum ore feeding angle.
[0046] Specifically, the ore feeding method is divided into 5 levels, with feeding angles of 42°~42.8°, 40°~41°, 38°~39°, 36°~37°, and 33°~34°, corresponding to 1~3, 2~4, 2~4, 1~3, and 1~3 circles respectively. The coke feeding method is also divided into 5 levels, with feeding angles of 43°~44°, 40°~41°, 38°~39°, 34°~35°, and 32°~33°, corresponding to 1~3, 2~4, 2~4, 1~3, and 1~3 circles respectively.
[0047] In one specific embodiment of the present invention, the ore feeding method is divided into 5 levels, with feeding angles of 42.8°, 40.8°, 38.8°, 36.3°, and 33.3°, corresponding to 2, 3, 3, 2, and 2 rotations respectively. The coke feeding method is also divided into 5 levels, with feeding angles of 43.3°, 40.8°, 38.3°, 35.3°, and 32.3°, corresponding to 2, 3, 3, 2, and 2 rotations respectively. The center coke has an angle of 13°, corresponding to 4 rotations.
[0048] It should be noted that the ore platform is the angle difference between the outermost ring ore and the innermost ring ore; the coke platform is the outer ring coke angle minus the inner ring coke angle (excluding the central coke).
[0049] Low-grade iron powder and mineral powder usually have a high Ti content. According to the blast furnace burden structure of this invention, the Ti content in the molten iron will reach more than 0.1%, which will increase the viscosity of the molten iron, reduce its fluidity, and affect the permeability of the blast furnace and the output of molten iron.
[0050] The blast furnace feeding method provided by this invention can form a structure in which coke coats the ore, promote the uniformity of mixing between coke and sinter, promote the full reduction of sinter by coke, and achieve a reduction and pulverization rate of over 68% for sinter. Furthermore, the full progress of the reduction reaction helps to form molten iron filings and slag at the top of the blast furnace, which facilitates the smooth flow of materials and gases within the blast furnace, promotes the smooth operation of blast furnace smelting, and ensures the output of molten iron.
[0051] Furthermore, during the smelting process, the temperature of the molten steel entering the converter is ≥1350℃, and then the temperature of the molten steel is raised to 1400℃~1450℃ within 80s~100s for converter smelting.
[0052] By using rapid heating, the oxidation of vanadium in the molten iron during the smelting process can be reduced, the vanadium content in the molten iron can be increased, and the amount of ferrovanadium alloy added can be reduced.
[0053] This invention comprehensively considers the quality of sintered ore, the smooth operation of blast furnace smelting, and the improvement of efficiency and quality in the entire process of iron smelting and steelmaking. It provides a novel vanadium-titanium sinter blending structure. By adjusting the blending structure and proportions, and using multiple raw materials mixed in specific amounts, it not only ensures the grade of sintered ore and the smooth operation of blast furnace smelting, but also makes full use of inexpensive low-quality iron ore resources and steel slag waste, thereby effectively reducing smelting costs. Simultaneously, the blending structure provided by this invention can effectively increase the vanadium content in the molten iron, reducing the amount of ferrovanadium alloy used. Furthermore, the steel slag obtained from smelting can be recycled as a raw material for the blending structure, reducing blending costs and waste generation. By adopting the unique blending structure, blast furnace charging, and smelting process provided by this invention, a comprehensive reduction in the cost of sintered ore raw materials, iron smelting, and steelmaking alloys is achieved. The cost of molten iron is reduced by 11 yuan / ton, and the cost of steelmaking is reduced by 0.68 yuan / ton. This improvement in quality while reducing overall process costs demonstrates high economic and environmental benefits and has significant potential for widespread application. Detailed Implementation
[0054] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0055] To better illustrate the present invention, further examples are provided below.
[0056] This invention provides a blast furnace charge structure, which includes a sintered ore blending structure and a blast furnace charge structure, comprising 70%~75% vanadium-titanium sinter, 15%~20% pellets, and 5%~15% lump ore.
[0057] The vanadium-titanium sinter has a particle size of 18-22 mm, the pellets have a particle size of 8-12 mm, and the lump ore has a particle size of 14-18 mm.
[0058] The raw materials for the vanadium-titanium sintered ore include sintered iron, flux, and fuel. Based on 100% of the vanadium-titanium sintered ore, the sintered iron material comprises the following raw material components by mass percentage: 4%~7% iron concentrate, 7%~11% high vanadium-titanium iron powder, 29%~40% external ore powder, 1%~2.5% steel slag, 0%~2% iron scale, 2%~3% aluminum powder, 1%~3% boron-magnesium iron powder, and 0%~2% pyrite powder; The flux comprises 1% to 1.5% limestone, 4% to 4.5% quicklime, and 5% to 5.5% dolomite powder; the fuel content is 3.5% to 4%.
[0059] The composition of each raw material in the sintered iron charge is shown in Table 1.
[0060] Table 1. Composition of each raw material (%) Option 1 The following method was used to prepare the sintered iron powder 1.
[0061] Ordinary iron powder 4%, 69 iron powder 2%, high vanadium iron powder 1 (Baotong) 2.5%, high vanadium iron powder 2 (Yuantong Jianlong) 3.5%, high vanadium iron powder 4 (Baitong Jianlong) 1.2%, high vanadium iron powder 5 (Luanping Jianlong) 1%, non-standard iron powder 3%, PB powder 6%, mixed powder 5.18%, 56 Indian powder 11%, super special powder 6%, Australian powder 3%, iron sheet 1%, aluminum powder 2.5%, boron-magnesium iron powder 1.5%, steel slag 1.8%, and degraded powder 1%.
[0062] The flux consists of 1% limestone, 4.2% quicklime, and 5.2% dolomite powder; 3.6% fuel coke powder; 11% overhead return ore, 14% internal return ore, and the remainder being gas ash and dust collector ash.
[0063] The internal return ore is the sinter that is screened after exiting the sintering machine. Ore ≥5mm enters the blast furnace rack, while ore <5mm is screened out and returned to the sintering process. In other words, the internal return ore is the sinter that is <5mm after sintering in the sintering machine. The sinter that enters the blast furnace rack is squeezed out of the rack and then screened again. Ore ≥5mm enters the blast furnace metallurgical process, while ore <5mm is rack return ore and returned to the sintering process.
[0064] The above-mentioned sintered ore components, such as sintered iron powder, flux, and fuel, are sintered according to the process shown in Table 2.
[0065] Table 2 Sintering parameters and technical specifications The blast furnace charging method is as follows: Ore charging: divided into 5 levels, with charging angles of 42.8°, 40.8°, 38.8°, 36.3°, and 33.3°, corresponding to 2, 3, 3, 2, and 2 rings respectively. Coke charging: divided into 5 levels, with charging angles of 43.3°, 40.8°, 38.3°, 35.3°, and 32.3°, corresponding to 2, 3, 3, 2, and 2 rings respectively. The center coke has an angle of 13°, corresponding to 4 rings.
[0066] During the smelting process, the temperature of the molten steel entering the converter is ≥1350℃, and then the temperature of the molten steel is raised to 1400℃~1450℃ within 80s~100s for converter smelting.
[0067] The composition of the sinter obtained from smelting, basicity R2, low-temperature reduction pulverization rate (referred to as low-temperature pulverization), vanadium content in molten iron, and cost of molten iron are shown in Table 3.
[0068] Table 3 Note: The test standard for low-temperature reduction pulverization rate is GB / T13242-91.
[0069] Option 2 The following method was used to prepare the sintered iron powder 2.
[0070] Ordinary iron powder 5%, 69 iron powder 2%, high vanadium iron powder 1 (Baotong) 2.5%, high vanadium iron powder 5 (Luanping Jianlong) 0.5%, non-standard card powder 3%, PB powder 6%, mixed powder 10.215%, 56 Indian powder 11%, super special powder 6%, Australian powder 3%, iron sheet 1%, aluminum powder 2.5%, boron magnesium iron powder 1.0%, and degraded powder 1%.
[0071] The flux consists of 1% limestone, 4.2% quicklime, and 5.2% dolomite powder; 3.6% fuel coke powder; 11% overhead return ore, 14% internal return ore, and the remainder being gas ash and dust collector ash.
[0072] The above-mentioned sintered ore components, such as sintered iron powder, flux, and fuel, are sintered according to the process shown in Table 4.
[0073] Table 4 Sintering parameters and technical specifications The blast furnace feeding and smelting methods shall be controlled in accordance with Scheme 1.
[0074] The composition of the sinter obtained from smelting, basicity R2, low-temperature reduction pulverization rate (referred to as low-temperature pulverization), vanadium content in molten iron, and cost of molten iron are shown in Table 5.
[0075] Table 5 Note: The test standard for low-temperature reduction pulverization rate is GB / T13242-91.
[0076] Option 3 The following method was used to prepare the sintered iron powder 3.
[0077] Ordinary iron powder 5%, 69 iron powder 2%, high vanadium iron powder 1 (Baotong) 2.5%, high vanadium iron powder 3 (Enshunqiang (Dingxin)) 2%, high vanadium iron powder 5 (Luanping Jianlong) 0.5%, non-standard iron powder 3%, PB powder 6%, mixed powder 8.445%, 56 Indian powder 11%, super special powder 6%, Australian powder 3%, iron sheet 1%, aluminum powder 2.5%, boron-magnesium iron powder 1.5%, steel slag 1.0%, and degraded powder 1%.
[0078] The flux consists of 1% limestone, 4.2% quicklime, and 5.2% dolomite powder; 3.6% fuel coke powder; 11% overhead return ore, 14% internal return ore, and the remainder being gas ash and dust collector ash.
[0079] The above-mentioned sintered ore components, such as sintered iron powder, flux, and fuel, are sintered according to the process shown in Table 6.
[0080] Table 6 Sintering parameters and technical specifications The blast furnace feeding and smelting methods shall be controlled in accordance with Scheme 1.
[0081] The composition of the sinter obtained from smelting, basicity R2, low-temperature reduction pulverization rate (referred to as low-temperature pulverization), vanadium content in molten iron, and cost of molten iron are shown in Table 7.
[0082] Table 7 Note: The test standard for low-temperature reduction pulverization rate is GB / T13242-91.
[0083] Option 4 The following method was used to prepare the sintered iron powder 4.
[0084] Ordinary iron powder 8.7%, 69 iron powder 2%, high vanadium iron powder 1 (Baotong) 2.5%, high vanadium iron powder 3 (Enshunqiang (Dingxin)) 2%, high vanadium iron powder 5 (Luanping Jianlong) 0.5%, non-standard iron powder 3%, PB powder 6%, mixed powder 5.065%, 56 Indian powder 11%, super special powder 6%, Australian powder 3%, iron sheet 1%, aluminum powder 2.5%, boron-magnesium iron powder 1.5%, steel slag 1.5%, and degraded powder 1%.
[0085] The flux consists of 1% limestone, 4.2% quicklime, and 5.2% dolomite powder; 3.6% fuel coke powder; 11% overhead return ore, 14% internal return ore, and the remainder being gas ash and dust collector ash.
[0086] The above-mentioned sintered ore components, such as sintered iron powder, flux, and fuel, are sintered according to the process shown in Table 8.
[0087] Table 8 Sintering parameters and technical specifications The blast furnace feeding and smelting methods shall be controlled in accordance with Scheme 1.
[0088] The composition of the sinter obtained from smelting, basicity R2, low-temperature reduction pulverization rate (referred to as low-temperature pulverization), vanadium content in molten iron, and cost of molten iron are shown in Table 9.
[0089] Table 9 Note: The test standard for low-temperature reduction pulverization rate is GB / T13242-91.
[0090] Option 5 The existing traditional ore blending schemes are as follows: Fuzhen Iron Powder 8%, Ordinary Iron Powder 7%, Iron Sheet 2%, Mixed Powder 18%, 56 Indian Powder 11%, Super Special Powder 5%, Degraded Powder 1%.
[0091] The V content in the molten iron obtained from smelting is 0.025%, and the cost of molten iron is 2612 yuan / ton.
[0092] The flux consists of 2.5% limestone, 4.6% quicklime, and 4.8% dolomite powder; 3.6% fuel coke powder; 11% overhead return ore, 15% internal return ore, and the remainder being gas ash and dust collector ash.
[0093] In summary, the blast furnace charge structure provided by this invention can minimize the amount of high-grade iron powder, which is more expensive, while ensuring that the quality of the sinter meets the requirements of blast furnace smelting. This not only ensures that the sinter has sufficient strength, but also greatly reduces the overall cost of the process, resulting in good economic benefits.
[0094] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A ore blending structure for a complete vanadium-titanium sinter process, wherein the raw materials for the vanadium-titanium sinter include sintered iron charge, flux, and fuel, characterized in that, Based on 100% of the vanadium-titanium sintered ore, the sintered iron material comprises the following raw material components by mass percentage: 4%~7% iron concentrate, 7%~11% high vanadium-titanium iron powder, 29%~40% external ore powder, 1%~2.5% steel slag, 0%~2% iron scale, 2%~3% aluminum powder, 1%~3% boron-magnesium iron powder, and 0%~2% pyrite powder; The iron concentrate includes ordinary iron powder and 69 iron powder; the high vanadium titanium iron powder has the following mass percentage composition: TFe 65%~67%, SiO2 2.6%~3.6%, CaO 0.9%~1.9%, MnO 0.08%~0.12%, MgO 0.2%~0.5%, Al2O3 0.8%~1.1%, TiO2 0.8%~2.2%, V 0.19%~0.24%, with the balance being unavoidable impurities; The mass percentage composition of the external mineral powder is as follows: TFe 55%~65%, SiO2 3.6%~6.6%, CaO 0.01%~0.21%, MnO 0.08%~0.8%, MgO 0.1%~0.17%, Al2O3 0.6%~5.9%, TiO2 0.02%~0.23%, V 0.001%~0.012%, with the balance being unavoidable impurities; Based on 100% of the vanadium-titanium sinter raw material, the content of ordinary iron powder is 3%~5%, and the content of 69 iron powder is 1%~2%; wherein, the mass percentage of the ordinary iron powder is: TFe 65%~67%, SiO2 4%~4.5%, CaO 1.3%~1.5%, MnO 0.08%~0.12%, MgO 0.3%~0.5%, Al2O3 0.7%~0.9%, TiO2 0.8%~1.0%, V 0.13%~0.14%, with the balance being unavoidable impurities; The 69 iron powder composition has the following mass percentages: TFe 68%~70%, SiO2 1.9%~2%, CaO 0.3%~0.5%, MnO 0.08%~0.12%, MgO 0.1%~0.3%, Al2O3 0.6%~0.7%, TiO2 0.6%~0.7%, V 0.08%~0.09%, with the balance being unavoidable impurities. The aluminum powder composition by mass percentage is as follows: TFe 47%~48%, SiO2 3.1%~3.2%, CaO 0.5%~0.7%, MnO 0.08%~0.12%, MgO 0.18%~0.2%, Al2O3 10%~12%, TiO2 4.1%~4.3%, V 0.11%~0.13%, with the balance being unavoidable impurities. The mass percentage of the degraded powder components is as follows: TFe 60%~61%, SiO2 3%~5%, CaO 0.1%~0.3%, MnO 0.1%~0.3%, MgO 0.1%~0.13%, Al2O3 2.1%~2.3%, TiO2 0.05%~0.07%, V 0.001%~0.003%, with the balance being unavoidable impurities; The mass percentage composition of the boron-magnesium-iron powder is as follows: TFe 54%~55%, SiO2 4%~6%, CaO 0.2%~0.4%, MnO 0.08%~0.12%, MgO 10%~11%, Al2O3 0.2%~0.3%, TiO2 0.08%~0.1%, V 0.004%~0.006%, with the balance being unavoidable impurities.
2. The ore blending structure of the entire process vanadium-titanium sinter as described in claim 1, characterized in that, The steel slag composition by mass percentage is as follows: TFe 21%~23%, SiO2 11%~13%, CaO 23%~25%, MnO 1%~3%, MgO 4%~6%, Al2O3 3%~5%, TiO2 2.5%~2.7%, V 0.84%~0.86%, with the balance being unavoidable impurities; The iron sheet composition by mass percentage is as follows: TFe 72%~73%, SiO2 1.4%~1.6%, CaO 0.01%~0.02%, MnO 0.2%~0.4%, MgO 0.1%~0.2%, Al2O3 0.9%~1.1%, TiO2 0.05%~0.07%, V 0.01%~0.03%, with the balance being unavoidable impurities.
3. The ore blending structure of the entire process vanadium-titanium sinter as described in claim 1, characterized in that, Based on 100% of the raw material of the vanadium-titanium sinter, the flux includes 1% to 1.5% limestone, 4% to 4.5% quicklime and 5% to 5.5% dolomite powder; the fuel content is 3.5% to 4%.
4. A method for blast furnace smelting of vanadium-titanium magnetite, the method comprising blast furnace smelting of blast furnace charge, characterized in that, The blast furnace charge includes the ore blending structure of the whole-process vanadium-titanium sinter as described in any one of claims 1 to 3.
5. The blast furnace smelting method for vanadium-titanium magnetite as described in claim 4, characterized in that, During the sintering process of the blast furnace charge, the material layer height is controlled at 790mm~810mm, the moisture content of the mixture is controlled at 7.1%~7.3%, the sintering machine speed is 2.1m / min~2.3m / min, the sintering speed is 19mm / min~20mm / min, the sintering temperature is 1250℃~1280℃, and the holding time is 120s~180s. The blast furnace charge distribution angles are as follows: ore platform angle is 5°~9.5°, coke platform angle is 8°~11°; the maximum coke distribution angle is greater than the maximum ore distribution angle, and the minimum coke distribution angle is less than the minimum ore distribution angle; there are 5~6 ore and coke levels, and as the level increases, the coke and ore distribution angles decrease sequentially, with the ore distribution angle between adjacent levels differing by 1°~3°, and the coke distribution angle between adjacent levels differing by 1°~3° except for the central coke; the central coke angle is 10°~15°, and the central coke accounts for 24%~26% of the total coke; During the smelting process, the temperature of the molten steel entering the converter is ≥1350℃, and then the temperature of the molten steel is raised to 1400℃~1450℃ within 80s~100s for converter smelting.
Citation Information
Patent Citations
Blast furnace smelting method of high-grade high-vanadium chromium-contained type vanadium-titanium iron ore concentrates
CN107312899A
Production method of boron-containing vanadium-titanium sintered ore
CN117127009A